AL QUR’AN DAN ISU KESETARAAN GENDER - Nurrochman, Nurrochman (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2014)
AbstractThis paper explains the issues Gender in al Qur’an and Islam. Adaptation of gender discourse in Islam have generated various respons among moslem, which can be classified in to at least three groups. First, outspoken group refuse the adaptation gender into moslem community. They have claimed gender issues represent the product of Western civilization and not a part of Islamic doctrine. Second, group that supporting adaptation of gender issues in Islam world. Third, critical group to issues gender in Islam. In one side, they active to campaign about gender equality in Islam world. But in the other side they also give the critic. This paper, focus on moslem feminists thougt, especially in al Qur’an interpretation. They attend in newly perspective about interpreting sentences of al Qur’an, especially that talking about the women rights, like polygamy, violence, justice, waris, divorce and veil usage. All of moslem feminists sure that Islam esteem the women rights. But, moslem intellectual have to reinterpretate the sentences of al Qur’an to get the deep meaning.Keywords: Islam, gender, tafsir